NARRATIVE REVIEW: PERCEPTION OF HEALTH PERSONNEL ON THE COMPETENCY OF THE PHARMACY PROFESSIONAL IN HOSPITAL - Anggia Paramita (Sean Institute, 2023)
Pharmaceutical services in the hospital environment have changed from being drugs oriented to being patient oriented in the sense that they are not only managing drugs but in a broader sense including providing information to support the correct and rational use of drugs, monitoring drug use to find out the goal, and the possibility of medication errors. There needs to be more research on nurses' perceptions of the role of pharmacists in Indonesia. Research on a similar topic was conducted by Alcantara (2018) in Brazil, namely Perceptions of a group of hospital pharmacists and other professionals of the implementation of clinical pharmacy at a high complexity public hospital in Brazil. Then research was conducted by Rayes (2016), a qualitative study exploring physicians' perceptions on the role of community pharmacists in Dubai. Research in Indonesia was conducted by Safitrih (2019) with the title Health Workers' Perceptions and Expectations of the Role of the Pharmacist in Emergency Units: A Qualitative Study in Kupang, Indonesia and research conducted by Meradiana (2021) on Perceptions of Health Workers in Collaborative Practices Interprofessional in Hospitals in Banyu Wangi, the articles used and meet the requirements based on the suitability of the topics, objectives, research methods, and research results of each article. The writing of this review article was carried out by conducting a literature study using scientific article sources. Searches were conducted online using the Google Scholar, PubMed, Elsevier, and ScienceDirect search engines with the keywords